2004
DOI: 10.1021/bi0483209
|View full text |Cite
|
Sign up to set email alerts
|

Parallel-Stranded Guanine Quadruplex Interactions with a Copper Cationic Porphyrin

Abstract: G-quadruplexes are formed by association of DNA strands containing multiple contiguous guanines. The capability of drugs to induce formation of or stabilize G-quadruplexes is an active area of investigation. We report the interactions of CuTMpyP4, the Cu(2+) derivative of 5,10,15,20-tetrakis(1-methyl-4-pyridyl)-21H,23H-porphine, with the parallel-stranded G-quadruplexes formed by d(T(4)G(4)T(4)) (1) and d(T(4)G(8)T(4)) (3). Absorption titrations of CuTMpyP4 with (1)(4) or (3)(4) cause both bathochromicity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 49 publications
(133 reference statements)
3
59
0
Order By: Relevance
“…We found that the absorbance was red shifted by less than 8 nm and that the hypochromicity was between 10 and 35 % for the interaction between the corroles and G4 DNA (Table 4). It is suggested that corroles 8, 9, and 12-15 have different binding modes compared with 3 and 4, [33] because of the increased bulkiness of the G4 DNA relative to corroles.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the absorbance was red shifted by less than 8 nm and that the hypochromicity was between 10 and 35 % for the interaction between the corroles and G4 DNA (Table 4). It is suggested that corroles 8, 9, and 12-15 have different binding modes compared with 3 and 4, [33] because of the increased bulkiness of the G4 DNA relative to corroles.…”
Section: Resultsmentioning
confidence: 99%
“…K b is the ratio of slope to the intercept. H% was calculated according to the following formula: [27]. The standard enthalpy change ( H • ), standard entropy change ( S • ) and standard free energy change ( G • ) of compounds 1-3 binding to DNAs were determined by van't Hoff's equation [28]:…”
Section: Absorption Spectra Titration and Uv-melting Experimentsmentioning
confidence: 99%
“…The percent hypochromisms (H%) of the maximum absorption band at 277 nm for the compounds 1-3 were all measured to be about 70%, and their bathochromism values ( ) were about 7 nm. While the significant hypochromism is in the range of intercalation binding, the observed bathochromism values are lower than that of typical intercalation interaction (≥15 nm) [27]. The intrinsic binding constants (K b ) for compounds 1-3 were all calculated in the order of 10 4 M −1 using Eq.…”
Section: Absorption Titration and Thermodynamicsmentioning
confidence: 99%
“…Their affinity is similar or even better than that of non-metalated porphyrin due to a lower electron density on the metalated porphyrin framework allowing higher stacking interaction with G-quartet. In contrast, octahedral complexes with two axial ligands on the metal that would pose a block to stacking interactions, exhibit lower affinity [71,103,112,[121][122][123][124][125]. Logically, due to their strong affinity for DNA duplex, none of these metalated TMPyP4 porphyrins are selective for G4 with respect to double-stranded DNA.…”
Section: Interaction Of Porphyrins With G-quadruplex Dnamentioning
confidence: 99%